2021
DOI: 10.1108/ilt-10-2020-0379
|View full text |Cite
|
Sign up to set email alerts
|

Restrictor-based studies of hybrid hole-entry conical journal bearings

Abstract: Purpose This paper aims to describe how successfully a particular restrictor delivers its best in increasing the conical journal bearing performance. The restrictors are used in the hole-entry conical journal bearing subjected to hybrid mode. Thus, the restrictors, like constant flow valve (CFV), orifice and capillary, are studied comparatively. Design/methodology/approach Numerical simulation for the bearing results with the three restrictors are obtained by using finite element method (FEM) under the well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In a study reported by Czaban, 9 the results were obtained at various bearing clearance and operating speed for hydrodynamic conical bearing. He concluded that accuracy of numerical simulation gets improved with inclusion of different effects but at the expense of computational cost Khakse et al 10 theoretically studied conical journal bearing with various flow control devices, like constant flow valve (CFV), orifice and capillary. They reported that the pressure in the circumferential direction is found to decrease for increased semi-cone angles, except for CFV hole-entry conical bearing.…”
Section: Conical Journal Bearing Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study reported by Czaban, 9 the results were obtained at various bearing clearance and operating speed for hydrodynamic conical bearing. He concluded that accuracy of numerical simulation gets improved with inclusion of different effects but at the expense of computational cost Khakse et al 10 theoretically studied conical journal bearing with various flow control devices, like constant flow valve (CFV), orifice and capillary. They reported that the pressure in the circumferential direction is found to decrease for increased semi-cone angles, except for CFV hole-entry conical bearing.…”
Section: Conical Journal Bearing Configurationmentioning
confidence: 99%
“…Texturing on bearing surface slightly increases the value of p. The reason for such behavior is that, due to the use of a micro-texture, the convergent and divergent regions are formed, and because of this feature there occurs a pressure drop in the divergent region which Table 2. Geometrical and operational parameters of hybrid conical porous journal bearing (3,8,10,11,14,26,38,40,46,47,(58)(59)(60).…”
Section: Lubricant Film Pressure ( P) Profilementioning
confidence: 99%
See 1 more Smart Citation
“…However, CHJBs are studied by very few researchers and hence scope for analysis and experimentation of it. Khakse et al (2016) and Khakse and Phalle (2021) used finite element analysis to compare the performance of orifice- and capillary-compensated non-recess hole-entry hybrid/hydrostatic conical bearing. The results showed that, non-recess orifice-compensated conical bearing gives better performance than the capillary-compensated restrictor.…”
Section: Introductionmentioning
confidence: 99%